KONSEP PENDIDIKAN ISLAM DALAM PEMIKIRAN K.H HASYIM ASY’ARI DAN TELAAH TERHADAP PROGRESIVISME - Eva M Seda Gadi; Muhammad Hanif; Syamsu Madyan (VICRATINA, 2020)
Seeing the reality of human life in the current era of globalization, ethical positions are often ignored and ruled out. The paradigm shift from education to teaching today makes people immersed in modernization, education is also dragged into the current that seems proposed to develop a whole human being. in the perspective of K.H Hasyim Asy'ari, educational goals must be in accordance with student goals. K. H Hashim believes that knowledge seeks part of noble work in religion, so people who seek knowledge must question and noble attitude to gain knowledge. the purpose of this research is to formulate the concept of Islamic education according to K.H Hasyim Asy'ari in progressivism. To achieve this goal, researchers use the literature review method by finding information and data from materials that are relevant to the objectives discussed. From the results of this study, it can be concluded that the concept of Islamic education according to K. Hasyim Asy'ari is to form a society that has morality.